Publicidad no convencional para mejorar la gestión de las relaciones con los clientes en la Empresa Golf Center S.A.C. ciudad de Huamachuco. - Polo Mauricio, Wilder Jhoel (2014)
In this enterprise has been realized the present research which mainly objective is support in what way the publicity can contribute to the relations to the clients. For this reason the problema is: in what way the no convetional publicity can contribute to improve the relations managements with the customers in the Enterprise Golf Center S.A.C., in the city of Huamachuco, year 2014?. To collect the data has been applied surveys to the sample of 17 current customers, the questions has permitted diagnostic that in this enterprise the publicity is not massive (radio, television, panels, etc.) on the contrary the publicity is applied by mail, person to person, use of catalogs, etc. The use of other questions has helped to investigate about the level of quality in the Administration of relations to the clients. Obtained the results, a serious discussion has been applied, besides appying a descriptive –transversal design ( or transactional ) of corretional type and folowinf a logic criteria. According to this results and a series of discussion, has being possible demonstrate the hypothesis: “The no conventional publicity don´t contribute in a positive way, creating conscience, informing persuading and inviting to improve the administration of the relation to the clients in the enterprise Golf center S.A.C., in the city of Huamachuco, year 2014”. This due to the very close relation to the media of both variables, following the logic rubrics of contrast. Finally, the conclusions and recommendations focus the advantages of the no conventional publicity, that permit to the enterprise create conscience to inform persuade and remember to the clients about the existence of its products.